Nutritional Quality, Proximate and Fatty Acid Compositions of Commercially Important Fish from Different Rivers in SE Türkiye: A Comparative Research - İhsan Ekin (Aquatic Sciences and Engineering)
Nutritional quality, proximate and fatty acid compositions of fish species from the Khabur, Ambar and Tigris Rivers in SE Türkiye were investigated for the first time. The fish with the lowest total lipids were Mastacembelus mastacembelus (0.93%) and Carasobarbus luteus (0.99%), and the fish with the highest total lipid was Chondrostoma regium from the Tigris River (7.47%). The highest cholesterol content was in Barbus lacerta (26.3 mg/100 g) and Capoeta umbla (29.98 mg/100g) of the Ambar Stream. However, the Tigris River Cyprinus carpio (7.9 mg/100g) and C. luteus (7.91 mg/100g) had the lowest cholesterol. The results showed that all species are good sources of ΣSFA and ΣMUFA, specifically C14:0, C16:0, C18:0, C16:1ω7 and C18:1ω9. However, the fish were poor for ω6 and ω3, particularly C20:4ω6, C20:5ω3 and C22:6ω3, probably due to hot water adaptation in summer. Nevertheless, C. carpio (Tigris River) and A. mossulensis (Khabur River) had relatively high ΣPUFA. Among all the fish, C. regium and A. mossulensis from the Khabur River were good for protein, and M. mastacembelus, C. luteus, C. carpio and C. trutta from the Tigris River can be recommended as lean fish. Finally, the results could be useful for fisheries industries and they could also guide studies of nutrition and fish physiology.